2020
DOI: 10.3390/nu12020332
|View full text |Cite
|
Sign up to set email alerts
|

Carrot Intake and Risk of Colorectal Cancer: A Prospective Cohort Study of 57,053 Danes

Abstract: Carrots are consumed worldwide. Several meta-analysis studies on carrot consumption have indicated that carrots play a central role as a protecting vegetable against development of different types of cancers. A cancer-preventive role of carrots is plausible because they are the main dietary source of the bioactive polyacetylenic oxylipins falcarinol (FaOH) and falcarindiol (FaDOH), which have shown anti-proliferative and anti-inflammatory activity in numerous in vitro studies. In addition, purified FaOH and Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…The dose for an optimal antineoplastic effect was found to be from 7 to 35 µg of falcarinol and falcarindiol/g feed in the rat model of CRC. However, effects are observed at even lower concentrations (Table 3) and it appears that a cancer-preventive dose of polyacetylenes in humans, based on this preclinical trial, can be achieved with a daily intake above 30 g raw carrots [52,130], which is in accordance with the results of the cohort study mentioned in Section 2.3.1. Table 3.…”
Section: In Vivo Studies Of the Chemopreventive Effect Of Falcarinol supporting
confidence: 87%
See 2 more Smart Citations
“…The dose for an optimal antineoplastic effect was found to be from 7 to 35 µg of falcarinol and falcarindiol/g feed in the rat model of CRC. However, effects are observed at even lower concentrations (Table 3) and it appears that a cancer-preventive dose of polyacetylenes in humans, based on this preclinical trial, can be achieved with a daily intake above 30 g raw carrots [52,130], which is in accordance with the results of the cohort study mentioned in Section 2.3.1. Table 3.…”
Section: In Vivo Studies Of the Chemopreventive Effect Of Falcarinol supporting
confidence: 87%
“…The latter has recently been confirmed in a prospective cohort study, examining the risk of being diagnosed with CRC, as predicted by intake of carrots in a Danish population of 57,053 individuals with a long follow-up [130]. Self-reported intake of raw carrots at a baseline of 2-4 carrots or more each week (> 32 g/day) was associated with a 17% decrease in risk of CRC with a mean follow-up of > 18 years, compared to individuals with no intake of raw carrots [130]. The results of this prospective cohort study clearly support the results of the antineoplastic effects observed for the major polyacetylenic constituents in carrots in a rat model of CRC, as discussed in Section 4.1.…”
Section: Cytotoxic C 17 and C 18 Acetylenic Oxylipins From Other Planmentioning
confidence: 73%
See 1 more Smart Citation
“…Carrot consumption has been inversely associated with various health outcomes, including colorectal cancer ( 30 ), lung cancer ( 31 ), prostate cancer ( 32 ), breast cancer ( 33 ), and stroke mortality ( 34 ). However, in our study, we failed to find a significant association between carrot intake and bladder cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective cohort study, examining the risk of being diagnosed with CRC as predicted by intake of carrots in a Danish population of 57,053 individuals with a long follow-up confirmed the cancer preventive effect of this vegetable. This preventive effect of carrot intake on CRC development is possibly due to the content of FaOH and FaDOH ( Deding et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%